Exploring spatial relationship in criminal behavior: A spatial analysis of offenders’ homes and theft locations in Kuching, Sarawak, Malaysia - Norita Jubit; Tarmiji Masron; Ryoji Soda; Azizul Ahmad; Mohd Norarshad Nordin (ResearchGate, 2025)
This study aims to identify the proximity of offenders' homes to the theft location in Kuching, Sarawak. The attribute data includes the total number of theft offenders in Kuching in 2018, categorized as solo and co-offenders. It also details the modus operandi used in these thefts, as well as the offenders' employment and educational backgrounds. At the same time, spatial data consists of Kuching and Samarahan land use types, Kuching police station sector boundaries, the home addresses of offenders, and the locations where thefts occurred. This study applied standard deviation ellipses, Euclidean distance analysis, and kernel density estimation. The findings indicate that young people and individuals in their late twenties (15-29 year olds) are at a higher risk of engaging in theft activities. Their target areas are often close to their homes, particularly in urban areas lacking CCTV and security guards. Offenders in urban areas, who are unemployed at the age of 15-29 years old and have low education (SPM level), tend to be thieves. Both solo offenders and co-offenders tend to commit theft near their home. The total number of solo offenders of theft is 78.5%, and co-offenders are 21.4%. The analysis reveals a high level of spatial clustering among offenders, with their homes concentrated in the urban center of Kuching, where crime is most prevalent. The findings imply that offenders' residences are localized in specific urban areas rather than being evenly distributed across the districts of Kuching, Sarawak. The offenders typically travel short distances when engaging in property crime, especially theft. The study suggests that land use planning should consider the concentration of offenders in urban areas. The study also highlights the importance of targeted patrols in high-crime urban areas, especially those lacking CCTV and security guards.